Data Collection and Intervention Personalized as Interactive Multimedia Documents - Rodrigues, Kamila R. H.; Viel, Caio César; Zaine, Isabela; Cunha, Bruna C. R.; Scalco, Leonardo F.; Pimentel, Maria G. C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
Mobile computing can be a facilitator for collecting data due to the fact that users carry their smartphones almost everywhere and all the time and because they can collect a wide range of data – textual, audiovisual and data collected automatically by sensors. Considering this opportunity, we developed the ESPIM (Experience Sampling and Programmed Intervention Method), an computeraided method for programming multimedia data collection forms and carry out remote interventions. Using the ESPIM, professionals of areas such as healthcare and education can plan data collection and define intervention programs using methods and procedures from their own areas. The programs containing the queries and tasks are retrieved by a mobile application installed in the devices of users who participate in the data collection. The mobile application runs the programs according to queries and tasks planned by the specialists. Both queries and responses can contain text, audio, and video data. In this paper we discuss about the technological infrastructure used in ESPIM system and also about the preliminary results obtained through tests and evaluation carried out with stakeholders of the target population. These results allowed us carried out improvements in the system.